Patient outcomes from a student-led interprofessional clinic in primary care. Issue 4 (July 2013) - Kent, Fiona; Keating, Jennifer
Abstract : A student-led clinic was established to investigate the potential for undergraduate students to deliver primary care to older people recently discharged from acute hospital admission. Patients older than 70 years, recently discharged from hospital to home, were invited to attend an interprofessional student-led outpatient clinic for review of physical, functional and social health needs. Teams of final year students from dietetics, medicine, nursing, occupational therapy, physiotherapy and social work reviewed 25 patients over an eight-week period. Using a standardized screening tool, student teams identified factors affecting health or independence and made referrals for relevant support. Patient perceptions of the consultation, measured with the Patient Experience Questionnaire, indicated that this was a very well-received patient-centered intervention and that the student teams provided useful information and education about self-management strategies.